A hierarchical procedure for the combination of forecasts - Mauro Costantini; Carmine Pappalardo (Institute for Advanced Studies (IHS), 2009)
This paper proposes a strategy to increase the efficiency of forecast combination. Given the availability of a wide range of forecasts for the same variable of interest, our goal is to apply combining methods to a restricted set of models. To this aim, a hierarchical procedure based on an encompassing test is developed. Firstly, forecasting models are ranked according to a measure of predictive accuracy (RMSFE). The models are then selected for combination such that each forecast is not encompassed by any of the competing forecasts. Thus, the procedure aims to unit model selection and model averaging methods. The robustness of the procedure is investigated in terms of the relative RMSFE using ISAE (Institute for Studies and Economic Analyses) short-term forecasting models for monthly industrial production in Italy.
Keywords: C32; C53; 330; combining forecasts; econometric models; evaluating forecasts; models selection; time series; Prognoseverfahren; Ökonometrisches Modell; Modellierung; Zeitreihenanalyse; Schätzung; Welt